Static and dynamic analysis methods of position-keeping capability for offshore supply vessels with voith-schneider propellers - Detlefsen, Ole; Theilen, Lasse; Abdel-Maksoud, Moustafa (Volume 1: Offshore Technology, 2017)
This paper presents a static and a time-domain method to assess the position-keeping capability of monohull vessels. For the static analysis method, the equlibrium between mean environmental loads and available actuator forces is determined. In case of the dynamic assessment, the motions of the fully actuated ship in all degrees of freedom are simulated in time domain and evaluated by criteria regarding the position and heading of the ship. After first results from validation tests an exemplary application is shown by assessing the positioning capability of a Voith-Schneider propelled offshore supply vessel.